DIFFERENT MODULES OF HOSPITAL MANAGEMENT SYSTEMS IN INDIA - Rana, Sachi; Mehta, Santosh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The healthcare sector in India is experiencing a digital revolution, with Hospital Management Systems (HMS) playing a pivotal role in transforming the way hospitals manage their operations. HMS serves as an integrated solution, comprising various modules that cater to clinical, administrative, and financial needs. This paper explores the different modules of HMS widely implemented in Indian hospitals, emphasizing their functionalities, benefits, and challenges. Key modules such as patient registration, electronic health records (EHR), pharmacy management, laboratory information systems (LIS), billing and insurance management, and telemedicine are analyzed. The study highlights how these modules streamline hospital workflows, reduce operational inefficiencies, and improve patient outcomes. By providing a detailed overview of HMS modules and their impact, this paper aims to contribute to the growing body of knowledge on digital healthcare transformation in India and offer insights for stakeholders to enhance healthcare delivery systems.